The recognition and modelling of a backbone and its deformity - Markauskas, Ramūnas; Juozapavičius, Algimantas; Saniukas, Kęstutis; Bernotavičius, Giedrius (Nonlinear Analysis: Modelling and Control, 2014)
In this article the authors present a method for the backbone recognition and modelling. The process of recognition combines some classical techniques (Hough transformation, GVF snakes) with some new (authors present a method for initial curvature detection, which they call the Falling Ball method). The result enables us to identify high-quality features of the spine and to detect the major deformities of backbone: the intercrestal line, centre sacral vertical line, C7 plumbline; as well as angles: proximal thoracic curve, main thoracic curve, thoracolumbar/lumbar. These features are used for measure in adolescent idiopathic scoliosis, especially in the case of treatment. Input data are just radiographic images, meet in everyday practice.
Keywords: active contours; Hough; Falling Ball; mathematical modelling of the backbone; adolescent idiopathic scoliosis; spinal deformities; recognition